Effect of Local Food–Based Supplementary Feeding on Body Weight among Toddlers in the Catchment Area of Marusu Primary Health Center - Eritariani; Suaib, Fatmawaty; Sirajuddin (Papua Medicine and Health Science, 2025)
Underweight is defined as low body weight resulting from undernutrition and reflects the failure of infants and toddlers to achieve ideal body weight. The occurrence of underweight among toddlers is primarily caused by inadequate nutrient intake, which is largely associated with households’ inability to provide sufficient food for all family members, limited access to food, poor dietary patterns including food taboos, and low household income. This study aimed to determine the effect of local food–based supplementary feeding on body weight among underweight toddlers at the Marusu Primary Health Center. This study employed an analytic observational design with a cross-sectional approach and was conducted in July 2025 using secondary data. A total of 58 underweight toddlers were included through total sampling, and the data were analyzed using the Wilcoxon Signed Rank Test. Prior to the intervention, all toddlers were classified as underweight. Following the provision of local food–based supplementary feeding, 17 toddlers (29.3%) showed an improvement in nutritional status and achieved normal body weight. Statistical analysis indicated a significant effect of supplementary feeding on the nutritional status of underweight toddlers (p-value < 0.05). In conclusion, local food–based supplementary feeding was proven to be effective in increasing toddlers’ body weight and improving mothers’ knowledge regarding the importance of adequate nutrition for children’s growth and development.